La gestión eficaz del conflicto y la mediación para mejorar la convivencia escolar (2017)
The present case study, unique, descriptive, naturalistic and qualitative, seeks to understand the effectiveness of strategies used by a teacher in mediating the conflicts between their students in cycle III and how they are solved. Through participant observation information was obtained from three predetermined categories such as the handling of emotions, clarification of the problem and the generation of solutions. Each category corresponds to the three basic phases of the mediation process in which citizens' competences are present. The data show that mediation was ineffective in the four episodes observed. The reflection was directed towards the way the teacher performs the process. It is concluded that for the constructive resolution of conflicts is a practice that is part of the school culture, it is essential to turn conflict into an opportunity for dialogue and improvement; Learn and develop skills that require the role of mediator teacher and the step by step of mediation...